2020
DOI: 10.1039/d0cc05658h
|View full text |Cite
|
Sign up to set email alerts
|

MmfL catalyses formation of a phosphorylated butenolide intermediate in methylenomycin furan biosynthesis

Abstract: Using a combination of a synthetic substrate analogue and product standard, MmfL, a homologue of the γ-butyrolactone biosynthetic enzyme AfsA, was shown to catalyse the condensation of dihydroxyacetone phosphate with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The phosphorylated butenolide product of the PBS domain is analogous to the intermediate in A‐factor biosynthesis produced by AfsA. The same kind of intermediate has been shown to be formed by MmfL (another AfsA homologue) in the biosynthesis of the methylenomycin furans [42] . Thus, it appears that phosphorylated 2‐acyl‐3‐hydroxymethylbutenolide intermediates are involved in the biosynthesis of structurally diverse natural products, including GBLs, AHFCAs, AHMBs and gladiostatin.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The phosphorylated butenolide product of the PBS domain is analogous to the intermediate in A‐factor biosynthesis produced by AfsA. The same kind of intermediate has been shown to be formed by MmfL (another AfsA homologue) in the biosynthesis of the methylenomycin furans [42] . Thus, it appears that phosphorylated 2‐acyl‐3‐hydroxymethylbutenolide intermediates are involved in the biosynthesis of structurally diverse natural products, including GBLs, AHFCAs, AHMBs and gladiostatin.…”
Section: Resultsmentioning
confidence: 95%
“…Domain and module organization of the gladiostatin trans‐AT PKS showing the proposed structure of each ACP‐bound thioester intermediate. KS domains have been numbered sequentially, and the TransATor [42] predictions for their acyl‐ACP substrates are shown in the dashed box. Modules are labelled M1, M2 etc.…”
Section: Resultsmentioning
confidence: 99%
“…These include the SRBs and the SABs,w hich contain as imilar butenolide moiety to gladiostatin (6). In addition to the PBS (SabA), aphosphatase (SabP) and aketoreductase (SabD) are known to be required for SAB biosynthesis,b ut the mechanism for [42] predictionsf or their acyl-ACP substrates are shown in the dashed box. Modules are labelled M1, M2 etc.…”
Section: Forschungsartikelmentioning
confidence: 99%
“…Thesame kind of intermediate has been shown to be formed by MmfL (another AfsA homologue) in the biosynthesis of the methylenomycin furans. [42] Thus,i ta ppears that phosphorylated 2-acyl-3-hydroxymethylbutenolide intermediates are involved in the biosynthesis of structurally diverse natural products,i ncluding GBLs, AHFCAs,A HMBs and gladiostatin. However,w ith the exception of GBLs,f urther work is needed to understand the mechanisms by which these intermediates get elaborated into the final metabolic products.…”
Section: Forschungsartikelmentioning
confidence: 99%
“…As previously shown for structurally related methylenomycin furan (MMF) autoinducers ( 48 ), AfsA-dependent biosynthetic pathways can also lead to furanoid formation ( 46 ). Analogously, we found that feeding of glycerol-1,1,2,3,3-d5 led to incorporation of a single deuterium in the furan core next to the ring oxygen (figs.…”
Section: Reconstruction Of Ancient Bgc Delivers Previously Unobserved...mentioning
confidence: 88%